Allergic reactions during childhood vaccination and management - Aytekin, Elif Soyak; Şekerel, Bülent E; Şahiner, Ümit M (The Turkish Journal of Pediatrics, 2021)
Background. Vaccination is one of the most effective public health tools to prevent a variety of infectious diseases. However, concerns about vaccine related adverse effects cause difficulties in clinical practice. Methods. This review was prepared based on the latest literature available in the PUBMED database in English language (as of March 2021), and all articles with the keywords pediatric vaccine, allergy, hypersensitivity, adverse reaction were evaluated to prepare the article. Results. Vaccine related confirmed allergic reactions are rare in children, ranging between 0,65-1.45 cases per million vaccine doses. Most of the allergic reactions are self-limited local reactions although in some cases severe anaphylaxis with multisystem involvement can be observed. Allergic reactions may occur because of either the active component (the antigen) of the vaccine, or additional components, such as preservatives, adjuvants, antimicrobials, stabilizers and other substances. Finding the culprit allergen is necessary to prevent future exposure to the allergen and to use alternative vaccines if possible. Diagnosis is largely based on a detailed history and clinical manifestation; also in vivo and in vitro tests may be helpful. Conclusions. In this review we provide information about hypersensitivity reactions to allergen components of childhood vaccines along with the diagnosis and management of vaccine allergy. Besides the tremendous benefits of vaccination for the health of children, we emphasized that the risk of adverse effects is rare and poses a negligible threat.